Study of antecedents and risk factors of preterm labour at a tertiary care hospital - Mukadam, Afrah Khalid; Sumondy, Spenta Jawahar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Preterm labor is an obstetrics emergency and a threat to population health. The 75% of infant mortality is related to preterm labor. Preterm labor not only inflicts financial and emotional distress on the family, it may also lead to permanent disability (physical or neurological damages) in infants. Aim and objectives were to assess the antecedents and risk factors for preterm labour and their preventive aspects and timely diagnosis of preterm labour, close monitoring and management of labour and providing neonatal care. Methods: Study design was of prospective study. Study setting was of department of obstetrics and gynecology at tertiary care centre. Study duration from 18 months, study population included were patients getting admitted in preterm labour in hospital during study period. Sample size was of 50. Results: Mean age of the mothers was 29.7±5.1 years, ranging from 20 to 43 years. It was observed that 84% of the patients were in the age group of 21 to 35 years. 16% of the mothers had GA less than 28 weeks, 28% had GA of 28 to 32 weeks and rest 56% of the mothers had GA of 32 to 37 weeks. Half of all mothers were primigravida, 28% were gravida 2 and rest 22% were gravida 3 or higher. 6% cases with fibroid, 4% had bicornuate uterus and one case had septate uterus. Surgical history of Dilation and curettage in 18%, previous LSCS in 14% and hysterolaparoscopy in 6%. Conclusions: It is recommended that specialized antenatal care for the patients, who are thought to be at risk of preterm birth, should be performed that can bring down the incidence to some extent.